Experimental and quantum chemical studies of functionalized tetrahydropyridines as corrosion inhibitors for mild steel in 1 M hydrochloric acid - Haque J.; Verma C.; Srivastava V.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
Corrosion inhibition property of ethyl 1,2,6-triphenyl-4-(phenylamino)-1,2,5,6-tetrahydropyridine-3-carboxylate (THP-1) and ethyl 2,6-bis(4-methoxyphenyl)-1-phenyl-4-(phenylamino)-1,2,5,6-tetrahydropyridine-3-carboxylate (THP-2) on mild steel (MS) in 1 M HCl have been studied using weight loss, electrochemical, surface morphology (SEM, AFM) and quantum chemical (QC) calculations methods. Results showed that both the functionalized tetrahydropyridines act as an excellent inhibition for mild steel (MS) and it exhibited the maximum inhibition efficiency (IE) of 90.67% (THP-1) and 94.30% (THP-2) at 7.95 × 10−5 M concentration. Results further showed that adsorption of THPs on metallic surface obeyed the Langmuir adsorption isotherm. Potentiodynamic polarization (PDP) study revealed that studied compounds acted as mixed type inhibitors. Electrochemical impedance spectroscopy (EIS) study suggests that the investigated inhibitors inhibit corrosion by adsorbing at the metal/electrolyte interfaces. The SEM, EDX and AFM studies showed that the THPs form a protective covering over the metallic surface that isolates the metal from aggressive acid solution and thereby protect form corrosive dissolution. Quantum chemical (QC) calculations carried out using DFT methods for neutral, solvated and protonated forms of inhibitors provides reasonable support to the experimental findings. © 2018 The Authors